Roof cooling techniques : a design handbook - Yannas, Simos; Erell, Evyatar; Molina, Jose Luis. (London : Earthscan, 2006)
Accompanying CD-ROM contains ... "software that enables readers to evaluate their own designs."--P. [4] of cover.
Includes bibliographical references and index.
Keywords: Roofs -- Cooling; Roofs -- Design and construction; Roofs -- Thermal properties; Buildings -- Environmental engineering